Atypical presentation of paroxysmal nocturnal hemoglobinuria treated by eculizumab: A case report. Issue 12 (March 2017) - Quinquenel, Anne; Maestraggi, Quentin; Lecoq-Lafon, Carinne; Régis, Peffault de Latour; Delmer, Alain; Servettaz, Amélie
Abstract: Rationale: Paroxysmal nocturnal hemoglobinuria (PNH) is a nonmalignant acquired hematopoietic stem cell disease, which can be revealed by hemolytic anemia, thromboembolism, or bonemarrow failure. Thrombosis can occur at any site, but coronary thrombosis is extremely rare. Controlled trials have demonstrated that eculizimab, an inhibitor of the terminal complement cascade, was able to reduce both hemolysis and thrombosis, but its efficacy in cases of PNH with coronary thrombosis is unknown. Patient concerns and diagnoses: We report herein the unusual case of a 73-year-old patient presenting with recurrent coronary syndromes without associated stenosis, fever, marked inflammatory syndrome, and anemia, leading to a delayed diagnosis of PNH. Intervention and outcomes: Eculizumab allowed the resolution of fever and inflammation, and prevented further thromboembolism. Lessons: This case emphasizes the importance of performing aflow cytometry test for PNH in front of unusual or unexplained recurrent thromboses. Thromboses, as observed in our case, may be associated with fever and marked inflammation. This case also provides useful information on eculizumab ability to prevent further thromboembolism in PNH patients with a medical history of arterial thrombosis.